2014
DOI: 10.1111/bdi.12244
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of inflammation in the central nervous system in patients with bipolar disorder

Abstract: We found evidence for increased production of antibody in the CSF of individuals with BD. However, the trend for polyspecific intrathecal antibody synthesis, as well as the presence of oligoclonal bands, might indicate activation of the intrathecal humoral immune system in a subgroup of patients with BD, as it is known to be associated with autoimmune disorders of the CNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 34 publications
2
45
0
Order By: Relevance
“… 4 6 , 8 The patient reported here had no history of being treated with immunosuppressants. His blood examination showed normal cell count despite of the presence of anti-CMV IgG and anti-HSV-II IgM in CSF, which is in accordance with the reported evidence for increased production of antibodies against several neurotropic infectious pathogens including HSV-I, HSV-II, and CMV, in the CSF of individuals with bipolar disorder 9 or autism spectrum disorders. 10 , 11 The mild signs of CNS inflammation in this patient may account for the absence of seizures and focal neurological signs although he presented primarily acute psychotic symptoms and mental status changes.…”
Section: Discussionsupporting
confidence: 88%
“… 4 6 , 8 The patient reported here had no history of being treated with immunosuppressants. His blood examination showed normal cell count despite of the presence of anti-CMV IgG and anti-HSV-II IgM in CSF, which is in accordance with the reported evidence for increased production of antibodies against several neurotropic infectious pathogens including HSV-I, HSV-II, and CMV, in the CSF of individuals with bipolar disorder 9 or autism spectrum disorders. 10 , 11 The mild signs of CNS inflammation in this patient may account for the absence of seizures and focal neurological signs although he presented primarily acute psychotic symptoms and mental status changes.…”
Section: Discussionsupporting
confidence: 88%
“…The patient described here had no history of being treated with immunosuppressive therapy. Although CSF had a fairly high cytosis, her blood examination showed normal cell count despite the presence of anti-VCA EBV IgG and anti-HSV-1/2 IgG in CSF, which is in accordance with the reported evidence for increased production of antibodies against several neurotropic pathogens including HSV-1/2, in the CSF of patients with bipolar disorder or autism spectrum disorders [10,11]. The absence of seizures and rough focal neurological signs characteristic of Herpes simplex encephalitis (HSE) confirm a mild process flow in the patient.…”
Section: Fig 1 Flair and T2 Weighted Images Of Mri Brain Showing Arsupporting
confidence: 89%
“…Another study found increased lactate levels in 5 out of 15 patients with bipolar disorder [ 13 ]. In an earlier study, we detected a synthesis of polyspecific, intrathecal antibodies against different neurotropic infectious pathogens ( Toxoplasma gondii , Herpes simplex virus types 1/2, cytomegalovirus, and Epstein–barr virus) in some patients with bipolar disorders [ 14 ].…”
Section: Introductionmentioning
confidence: 99%